Storage Tank Fire - Boilover Study of Biodiesel/Biofuel - Saleh Alyafeai, Ali Abdullah (Universiti Teknologi PETRONAS, 2016)
An experimental study of boilover phenomena in connection with biodiesel pool fire is carried out to determine the possibility of biodiesel to boilover during a fire and the properties of the biodiesel during boilover, if it has the tendency to boilover such as time taken to boilover, relation between depth of the biodiesel and the time taken to boilover and the radius of the ejections during a boilover. A biodiesel is burned in steel pans ranging from a circular one with diameter of 15 cm and 19 cm. A biodiesel layer of 2, 2.5, 3, 3.5 and 4 cm will be floating on water in the pans.The burning of the biodiesel for all the set up ended with boilover i.e ejection of burning fuel and fire enlargement were observed for all the tests conducted. The time taken to boilover upon burning increases as the fuel depth increased. The tests using larger diameter container (19cm) produce faster time to boilover compared to the test using smaller diameter container (15cm) for the same fuel depth. On the different type of biodiesel, B7 (mixture of 7% biodiesel + 93% conventional diesel ) produces faster time to boilover compared to b100 ( 100% biodiesel).